Medication underuse headache - Wanakorn Rattanawong; Alan Rapoport; Anan Srikiatkhachorn (My University, 2024)
Background Many risk factors have been associated with migraine progression, including insufficient and ineffective utilization of migraine medications; however, they have been inadequately explored. This has resulted in suboptimal usage of medications without effective altering of prescribing recommendations for patients, posing a risk for migraine chronification. Methods Our aim is to conduct a comprehensive review of the available evidence regarding the underuse of migraine medications, both acute and preventive. The term “underuse” includes, but is not limited to: ( 1 ) ineffective use of appropriate and inappropriate medication; ( 2 ) underutilization; ( 3 ) inappropriate timing of usage; and ( 4 ) patient dissatisfaction with medication. Results The underuse of both acute and preventive medications has been shown to contribute to the progression of migraine. In terms of acute medication, chronification occurs as a result of insufficient drug use, including failure of the prescriber to select the appropriate type based on pain intensity and disability, patients taking medication too late (more than 60 minutes after the onset or after central sensitization has occurred as evidenced by allodynia), and discontinuation because of lack of effect or intolerable side effects. The underlying cause of inadequate effectiveness of acute medication lies in its inability to halt the propagation of peripheral activation to central sensitization in a timely manner. For oral and injectable preventive migraine medications, insufficient efficacy and intolerable side effects have led to poor adherence and discontinuation with subsequent progression of migraine. The underlying pathophysiology here is rooted in the repetitive stimulation of afferent sensory pain fibers, followed by ascending brainstem pain pathways plus dysfunction of the endogenous descending brainstem pain inhibitory pathway. Although anti-calcitonin gene-related peptide (CGRP) medications partially address pain caused by the above factors, including decreased efficacy and tolerability from conventional therapy, some patients do not respond well to this treatment. Research suggests that initiating preventive anti-CGRP treatment at an early stage (during low frequency episodic migraine attacks) is more beneficial than commencing it during high frequency episodic attacks or when chronic migraine has begun. Conclusions The term “medication underuse” is underrecognized, but it holds significant importance. Optimal usage of acute care and preventive migraine medications could potentially prevent migraine chronification and improve the treatment of migraine attacks.
Keywords: Discontinuation; Allodynia; Migraine treatment; Migraine and Headache Studies